Analysis of Solid Medical Waste Management in Health Centres and Its Impact on Environmental Health in Koto Tangah Aie Pacah District, Padang City, West Sumatera - Rahmalia Afriyani; Jernita Sinaga; Wijayantono (CV. Get Press Indonesia, 2025)
Proper management of solid medical waste is essential to prevent environmental and health hazards. Improper handling can cause pollution and spread diseases within nearby communities. Objective: This study analyses solid medical waste management in health centres and its impact on environmental health in Koto Tangah, Air Pacah District, Padang City, West Sumatera. Method: A descriptive survey with quantitative and qualitative approaches was conducted from January to June 2024. Data were collected through direct observation, in-depth interviews with 15 waste management officers from selected health centres, and secondary data from environmental and public health reports (2023). Results: The findings show that medical waste management in these centres remains below standard, particularly in sorting, storage, and disposal practices. These shortcomings may degrade environmental quality and increase the risk of infectious diseases among local residents. Implications: The study highlights the urgent need to enhance staff capacity, awareness, and adherence to standard operating procedures for medical waste management to reduce environmental risks. Conclusion: Medical waste management in health centres across Air Pacah Sub-district requires significant improvement to mitigate its adverse effects on environmental health and to promote a cleaner, safer, and healthier community environment.